POLITICAL WILL MAYOR OF KEDIRI IN OVERCOMING COVID-19 PANDEMICS - Khusnul Prasetyo; M. Bashroni Shidqon; Diah Ayu Rachma (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The COVID-19 pandemic urges the central government to develop various policies, rules, standards, guidelines, and criteria to deal with COVID-19, but the problem lies with local governments. Therefore, regional heads are required to use their political will to control COVID-19 cases and overcome the impacts caused by the COVID-19 pandemic. This study aims to analyze the political will of the Mayor of Kediri in overcoming the COVID-19 pandemic through the seven components of Brinkerhoff's political will. Using a qualitative approach which was analyzed descriptively. Data collection techniques were carried out by in-depth interviews and focus group discussions. The results show that the Mayor of Kediri has tried to use his power and authority to the maximum extent possible on the six components of political will, namely government initiative; priority/choice of policy; mobilization of stakeholders; public commitment and allocation of resources; continuity of effort; and learning and adaptation. But unfortunately weak in the component of the application of credible sanctions. The Mayor of Kediri feels the need to form experts in the field of law to improve the quality and quantity of legislation and conduct academic studies and discussions before deciding policies in the era of the COVID-19 pandemic to be effective and solution-oriented In addition, consistency in enforcing the rules, not half-way in carrying out road closure policies that seem just a formality is also a concern of researchers.